2018
DOI: 10.1029/2018jb016179
|View full text |Cite
|
Sign up to set email alerts
|

Making Cratonic Lithospheric Mantle

Abstract: The origin of cratonic lithospheric mantle has been attributed to either high‐pressure (5–7 GPa) melting in hot mantle plumes or low‐pressure (<5 GPa) melting in mid‐ocean ridges or suprasubduction zones. To resolve this long‐standing debate, it is necessary to confirm under what depths the incipient cratonic mantle melted. Compared with most cratonic mantle xenoliths and xenocrysts, which commonly experienced metasomatic modification after melt extraction, diamond inclusions with predominantly harzburgitic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 143 publications
(308 reference statements)
0
1
0
Order By: Relevance
“…The SCLM beneath the Archaean cratons is characterized by (a) comparatively low geothermal gradient, (b) higher thickness and density, and (c) lack of extensive convection-related mixing and it acts as a lid to the hot convecting asthenospheric mantle beneath. Geophysical studies over the years have shown that the SCLM is considered to be formed by accretion of arc and oceanic lithospheres (Lee, 2006;Pollack, 1986;Su & Chen, 2018). Besides, SCLM is the most heterogeneous and chemically distinct geochemical reservoir capable of generating melts with exotic compositions, such as, lamproites and orangeites (Chalapathi Rao, Creaser, Lehmann, & Panwar, 2013;Krmícek, Romer, Ulrych, Glodny, & Prevelic, 2016;Pearson & Nowell, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The SCLM beneath the Archaean cratons is characterized by (a) comparatively low geothermal gradient, (b) higher thickness and density, and (c) lack of extensive convection-related mixing and it acts as a lid to the hot convecting asthenospheric mantle beneath. Geophysical studies over the years have shown that the SCLM is considered to be formed by accretion of arc and oceanic lithospheres (Lee, 2006;Pollack, 1986;Su & Chen, 2018). Besides, SCLM is the most heterogeneous and chemically distinct geochemical reservoir capable of generating melts with exotic compositions, such as, lamproites and orangeites (Chalapathi Rao, Creaser, Lehmann, & Panwar, 2013;Krmícek, Romer, Ulrych, Glodny, & Prevelic, 2016;Pearson & Nowell, 2002).…”
Section: Introductionmentioning
confidence: 99%